Wi-Fi hotspot networks sprout like mushrooms. (IEEE spectrum)
What began as a plaything among technology buffs in the United States has quietly evolved into the fastest-growing wireless data application in the world. All over, networks based on the IEEE's 802.11b wireless local-area networking standard, known also by the commercial trademark Wi-Fi, have been springing up-and not only in businesses and other self-contained organizations but in public places like waiting rooms and coffee shops as well. Now, increasingly, service companies are stringing these "hotspot" networks together to create what could soon be the world's largest wireless data network. It is in Europe, however, where the creation of transregional Wi-Fi networks may be taking off the fastest and where opportunities and challenges are coming into sharpest relief. IEEE 802.11b has prompted some serious concern about its potential impact on third-generation mobile technologies. The Europeans have championed 3G cellular telephony in global standards organizations, as a successor to its hugely successful Global System for Mobile Communications (GSM).